2011
DOI: 10.1007/s00467-011-1811-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth of kidney-transplanted pediatric patients treated with sirolimus

Abstract: Experimental findings indicate that sirolimus (SRL) inhibits longitudinal growth by mechanisms potentially related to its inhibitory effects on both cell proliferation and expression of vascular endothelial growth factor (VEGF). The aim of this study was to investigate the growth pattern of kidney-transplanted children treated with SRL in a multicenter observational clinical study. Height, change in height SD (Δ height) and growth velocity of pediatric patients with renal transplant were calculated at 0, 6, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…Growth inhibition has been reported in kidney-transplanted pediatric patients receiving sirolimus. 13 In our case, the rate of height and weight gain was not changed by treatment. However, the long-term effect of everolimus on physical development of TSC patients is not known.…”
Section: Figurementioning
confidence: 42%
“…Growth inhibition has been reported in kidney-transplanted pediatric patients receiving sirolimus. 13 In our case, the rate of height and weight gain was not changed by treatment. However, the long-term effect of everolimus on physical development of TSC patients is not known.…”
Section: Figurementioning
confidence: 42%
“…24 Besides our study, somatic growth retardation by rapamycin has been observed in mouse embryos 16 and in young rats. 25 This phenomenon in children is controversial with one study finding adverse effects of rapamycin on growth of pediatric transplant recipients, 26 whereas another study found normal linear growth in a similar cohort. 27 On the other hand, similar doses of mTOR inhibitors seem to be better tolerated and not cause growth retardation in children without organ transplants or the concurrent use of multiple other immunosuppressive agents, for example, in the treatment of astrocytomas associated with tuberous sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study involving pediatric kidney transplant recipients undergoing treatment with rapamycin suggests that growth rate is reduced in the treated group, at least for the 2 y of data available. 55 Nevertheless, considering the severity of the disease, the benefits may outweigh the potential side effects, and perhaps they can be controlled with careful dosing schedules, for instance, intermittent periods of treatment, followed by recovery periods, rather than chronic treatment.…”
Section: Therapeutic Limitations Of Rapamycinmentioning
confidence: 99%